Assessing MSDs before Introduction of a Cobot: Psychosocial Aspects and Employee’s Subjective Experience - Cippelletti, Emma; Azouaghe, Soufian; Pellier, Damien; Landry, Aurélie (Relations industrielles / Industrial Relations, 2023)
Musculoskeletal disorders (MSDs) are one of the main causes of work disability (EU-OSHA, 2019; WHO, 2019). Several solutions, including the cobotic system (EUROGIP, 2017), have been put forward to improve unhealthy working conditions and prevent MSDs. We sought to identify the MSD risk factors of workers on a screen-printed glass production line prior to introduction of a cobot. We used a mixed data collection technique: video observations and assessment of MSD risk factors by expert ergonomists, and then self-confrontation interviews with six production-line operators and subjective perception of risk factors. The two types of assessment (by experts and by operators) showed that the most demanding risk factors were physical (e.g., work posture) and psychosocial (e.g., mental workload). Certain risk factors were viewed differently by the experts and the operators. One question remains: How can a cobot make work more meaningful for operators?